Short-acting antipsychotics or long-acting injectables? A treatment comparison in patients with schizophrenia - Thiem, Helena; Folkerts, Here; Völkel, Lukas (Gesundheitsökonomie & Qualitätsmanagement, 2020)
Aim This research aims to compare the efficacy and direct costs of short-acting oral antipsychotics and aripiprazole once-monthly (AOM) in the context of the treatment of patients with schizophrenia based on real-world data in Germany.Method Results are based on a single-armed, retrospective, non-interventional pre-post comparison study evaluating data from 132 patients with schizophrenia before and after switching from oral antipsychotics to AOM treatment (6 months each). Socio-demographics, as well as parameters of indication, efficacy and resource consumption were analyzed and statistically evaluated.Results The switch from an oral antipsychotic medication to AOM led to a distinct improvement in all clinically relevant parameters, including a reduction in hospitalization rates (55.1 % vs. 14.0 %), length of stay (43.5 d vs. 34.8 d) and percentage of patients with multiple hospitalizations (13.6 % vs. 3.8 %). There was also a reduction in schizophrenic episodes for patients with ≥ 1 episode (2.9 vs. 1.4) and of the percentage of patients with ≥ 1 (88.0 % vs. 29.3 %) as well as ≥ 2 (60.0 % vs. 8.1 %) schizophrenic episodes. The proportion of patients requiring a visit to day clinics or psychiatric institute outpatient clinics (PIA) decreased (39.5 % vs. 8.4 %) for patients with AOM treatment, as did the average length of stay in day clinics or PIAs (116.8 d vs. 86.4 d) for patients with ≥ 1 stay. The cost saving potential of AOM compared to the treatment with oral antipsychotics ranged between 1,729.32 € and 5,048.53 € per patient for a six-month observation period.Conclusion Our results suggest that AOM treatment of patients with schizophrenia is more effective (reduction in schizophrenic episodes, hospitalizations, stays in day clinics, psychiatrist visits, losses in productivity) and generates lower costs for the statutory health insurance (SHI) in Germany than treatment with oral antipsychotics and should therefore not be regarded as only a last-resort treatment option for schizophrenia.
Keywords: Pre-Post Study; Schizophrenia; LAI; Hospitalization; Aripiprazole Once-Monthly